Risk Factors Associated With Reoperative Surgery for Thyroid Malignancies: A Retrospective Cohort Study. (29th January 2023) - Hutchinson, Kelly Ann; Guerra, André; Payne, Alexandra E.; Turkdogan, Sena; Forest, Veronique‐Isabelle; Hier, Michael P.; Payne, Richard J.
Abstract: Objective: To examine various factors associated with an increased risk of reoperation for persistent or recurrent malignant thyroid cancers. Study Design: Retrospective cohort study. Setting: Tertiary academic hospital centers. Methods: Patients undergoing surgery for thyroid cancer at 2 tertiary academic institutions from 2006 to 2020 were included. Those who underwent a reoperative procedure were compared with patients only requiring 1 procedure. The Pearson chi‐square and independent t test were used to compare group data accordingly. Furthermore, a binomial logistic regression was performed, while machine learning models were used to construct a predictive algorithm. Results: This study included 2266 patients with surgically managed thyroid malignancy, of which 54 (2.4%) necessitated reoperations. Those requiring a second surgical procedure were more likely to be male (40.7% vs 20.9%, P < .001), undergo bilateral (24.1% vs 3.3%, P < .001) and lateral (16.7% vs 1.8%, P < .001) neck dissections, and have a greater number of metastatic lymph nodes (mean, 9.1 vs 3.5; P < .001) and a larger tumor size (mean, 3.0 vs 2.0 cm; P < .001). According to the binomial logistic regression model, lateral neck dissection, greater number of metastatic lymph nodes, and larger tumor size significantly increased the odds of necessitating a second procedure by 7.8 (95% CI, 2.523‐24.083), 1.1 (95% CI, 1.032‐1.152), and 1.3 (95% CI, 1.064‐1.559), respectively. Last, machine learning models could not significantly predict the occurrence of reoperation. Conclusion: This study identified patient‐ and cancer‐related characteristics associated with an increased risk of requiring reoperation for thyroid malignancies.